Maps & globes - Knowlton, Jack.; Barton, Harriett (New York : Harper, 1986)
A brief history of mapmaking, a simple explanation of how to read maps and globes, and an introduction to the many different kinds of maps there are.
A Harper Trophy book.
"Reading Rainbow book."--Cover.
Accelerated Reader AR
Keywords: Maps -- Juvenile literature; Globes -- Juvenile literature; Maps; Globes